Estudo das propriedades químicas e antimicrobianas das soluções de hipoclorito de sódio - Morari, Víctor Hugo Carvalho (2012)
The objective of this study was to evaluate the dissolution of bovine pulp tissue by NaOCl solutions in different concentrations for a similar period to the time of root canal preparation, and chemical and antimicrobial properties of the resulting solution after this dissolution. Fragments of bovine dental pulp were exposed to different solutions (0.5, 1.0, 2.5 and 5.25%) for 10 minutes. Each one minute, the solution was renewed. The reduction of weight of fragment of pulp was measured. The antimicrobial activity of the solutions was evaluated against Enterococcus faecalis by agar diffusion test. Fresh NaOCl solution and the resulting solution of dissolution test were placed into wells prepared agar plates. After the incubation period, the inhibition zones of bacterial growth were measured with the aid of a digital caliper. The concentration of active chlorine initial and final was measured by iodometric titration. The hydrogen potential of the solutions was measured by digital pHmeter. Statistical analysis was performed by ANOVA, test and post hoc Tukey test for paired samples when appropriate (α <0.05). To check the correlation between concentration and rate of dissolution of pulp or percentage of weight reduction of pulp fragments, we employed the Pearson linear correlation. We found a significant association between concentration and dissolution rate of pulp (rPearson=0.9698, p=0.03). There was also a strong correlation between concentration and percentage of weight reduction of the fragments (rPearson=0.9843, p = 0.01). The hypochlorite solution with 5.25% showed the highest inhibition zones, followed by 2.5% NaOCl (p <0.01). There was no statistically significant difference between the concentrations of 0.5% and 1.0%. The inhibition zones reduced after dissolving pulp is not significant for the solution to 1.0% (p=0.1). After dissolving bovine pulp tissue, there was a significant reduction of the pH of the solutions at 0.5%, 1.0% and 5.25%, which kept the concentration of active chlorine dissolution. It is concluded that the higher the concentration of NaOCl, the greater its antimicrobial action against the E.faecalis and its effectiveness in dissolving pulp tissue. Can also be stated that the process of dissolving pulp reduces the antimicrobial effectiveness of sodium hypochlorite, probably due to the consumption of sodium hydroxide during the test.